Pengembangan Instrumen Penilaian Kepuasan Pasien terhadap Pelayanan Kefarmasian di Rumah Sakit - Dedy Almasdy; Yulihasri Yulihasri; Dila Deria Putri (Fakultas Farmasi Universitas Andalas, 2015)
Instrument to assessing patient satisfaction to hospital pharmacy services has developed. The instrument consists of two dimensions which are friendly explanation and managing theraphy. The result of instrument developing are a instrument which have fair to good of the level of agreement (ĸ = 0.53), fair to good validity (r > 0.632) and good reliability (cronbach alpha = 0.97).